The Pb isotopic evolution of the Martian mantle constrained by initial Pb in Martian meteorites - Bellucci, J.; Nemchin, A.; Whitehouse, M.; Snape, J.; Bland, Phil; Benedix, G. (2015)
The Pb isotopic compositions of maskelynite and pyroxene grains were measured in ALH84001 and three enriched shergottites (Zagami, Roberts Massif 04262, and Larkman Nunatuk 12011) by secondary ion mass spectrometry. A maskelynite-pyroxene isochron for ALH84001 defines a crystallization age of 4089 ± 73 Ma (2σ). The initial Pb isotopic composition of each meteorite was measured in multiple maskelynite grains. ALH84001 has the least radiogenic initial Pb isotopic composition of any Martian meteorite measured to date (i.e., 206Pb/204Pb = 10.07 ± 0.17, 2σ). Assuming an age of reservoir formation for ALH84001 and the enriched shergottites of 4513 Ma, a two-stage Pb isotopic model has been constructed. This model links ALH84001 and the enriched shergottites by their similar μ value (238U/204Pb) of 4.1–4.6 from 4.51 Ga to 4.1 Ga and 0.17 Ga, respectively. The model employed here is dependent on a chondritic μ value (~1.2) from 4567 to 4513 Ma, which implies that core segregation had little to no effect on the μ value(s) of the Martian mantle. The proposed Pb isotopic model here can be used to calculate ages that are in agreement with Rb-Sr, Lu-Hf, and Sm-Nd ages previously determined in the meteorites and confirm the young (~170 Ma) ages of the enriched shergottites and ancient, >4 Ga, age of ALH84001.